A Fixed-Dose Combination, QXOH/Levobupivacaine, Produces Long-Acting Local Anesthesia in Rats Without Additional Toxicity - Yin, Qinqin; Zhang, Yujun; Lv, Rong; Gong, Deying; Ke, Bowen; Yang, Jun; Tang, Lei; Zhang, Wensheng; Zhu, Tao (Frontiers in Pharmacology, 2019)
QXOH, a QX314 derivative with longer duration and lesser local toxicity, is a novel local anesthetic in preclinical drug development. Previous studies demonstrated that bupivacaine can prolong the effects of QX314. So, we attempted to combine QXOH with levobupivacaine to shorten the onset time and lengthen the duration. In this study, we investigated the efficacy, local and systemic toxicity in rats. In subcutaneous infiltration anesthesia, the inhibition of cutaneous trunci muscle reflex for QXOH-LB was greater than QXOH and levobupivacaine in the first 8 h (QXOH-LB vs. QXOH, P = 0.004; QXOH-LB vs. LB, P = 0.004). The completely recovery time for QXOH-LB (17.5 ± 2.5 h) was significantly longer than levobupivacaine (9.0 ± 1.3 h, P = 0.034) and QXOH (9.8 ± 0.9 h, P = 0.049). In sciatic nerve block, QXOH-LB produced a rapid onset time, which was obviously shorter than QXOH. For sensory, the time to recovery for QXOH-LB was 17.3 ± 2.6 h, which was statistically longer than 6.0 ± 1.8 h for QXOH (P = 0.027), and 4 h for levobupivacaine (P = 0.001). Meanwhile, the time to motor recovery for QXOH-LB was 7.9 ± 2.8 h, significantly longer than 4 h for levobupivacaine (P = 0.003) but similar to 6.0 ± 1.7 h for QXOH (P = 0.061). In local toxicity, there was no significant difference of histological score regarding muscle and sciatic nerve in QXOH-LB, QXOH, levobupivacaine and saline (P < 0.01). In the combination, the interaction index of LD50 was 1.39, indicating antagonistic interaction between QXOH and levobupivacaine in terms of systemic toxicity. In this study, we demonstrated that QXOH-LB produced cutaneous anesthesia which was 2-fold greater than that produced by QXOH or LB alone, and elicited sciatic nerve block with a potency that was 5- and 3-fold that of LB and QXOH, respectively. Local tissue inflammation by QXOH-LB was mild, similar to that induced by LB. This fixed-dose combination led to an antagonistic interaction between QXOH and LB in terms of systemic toxicity. These results suggested that QXOH-LB induced a long-lasting local anesthesia, likely, avoiding clinically important local and systemic toxicities.